Teaching Neuroscience: A Primer for Psychotherapists - Cabaniss, Deborah L. (Frontiers in Behavioral Neuroscience, 2018)
Today, it is essential to incorporate neuroscience into any psychotherapy curriculum. However, most psychotherapy educators are not trained in neuroscience. This paper offers five papers that can help incorporate neuroscience into psychotherapy training, as well as pedagogical suggestions.